Analisis Market Demand Pembangunan Bandara Singkawang, Kalimantan Barat - Roza, Febria; Jati Utama, Risqi Wahyu; Adefertana, Risfando; Agustian, Yosia; Akbar, Rivaldo Maulana (Jurnal Sains dan Teknologi Penerbangan, 2025)
This study aims to analyze the market demand for the development of Singkawang Airport in West Kalimantan. Using the Fishbone Diagram approach, this research identifies six key categories that influence market demand: people, methods, machines, materials, environment, and management. Data for the study was obtained through literature reviews and interviews with relevant stakeholders such as local government, airport management, tourism industry players, and local communities. The study’s findings reveal that key factors influencing market demand include the improvement of infrastructure connecting to the airport, supporting government policies, and the rapid growth of the tourism sector. Additionally, the quality of airport services is an important factor in attracting tourists and supporting the local economy. Proposed solutions include enhancing the land transport network, implementing environmentally friendly technologies, and empowering local communities through skill development programs. This study is expected to provide strategic guidance for the government and stakeholders in planning an efficient, sustainable airport development project that can meet the growing market demands.